Urine Periostin Level and Renal Function in Malignancy Patients Treated with High-Dose Cisplatine - Yusuf, Harry; Rachman, Andhika; Marbun, M Bonar; Shatri, Hamzah; Ahadini, Putri Aliya (Folia Medica Indonesiana, 2024)
Cisplatin has been used extensively as a cancer treatment. Nephrotoxicity, which is assessed by blood urea levels, blood creatinine, and estimated glomerular filtration rate (eGFR), is caused by cisplatin metabolites that build up in the kidneys. Because of these indicators' numerous flaws, optimal biological markers are required. One of the key mediators of inflammatory processes, such as kidney fibrosis and inflammation, is periostin. In cancer patients undergoing high-dose cisplatin therapy, the purpose of this study is to ascertain how urine periostin changes and how it relates to kidney function. This cross-sectional study was carried out at the National Center General Hospital of Cipto Mangunkusumo's medical hematology-oncology outer clinic and medical hematology-oncology ward on the eighth floor starting in November 2019 and ending when the minimum sample was obtained through consecutive sampling. Data was analyzed by IBM SPSS Statistics for Windows version 23.0 based on the research objective. Of the 37 responders, 70.3% were men, 29.7% were between the ages of 41 and 50, 78.4% were married, 59.5% had completed high school, 37.8% were employed, 59.5% had NPC, and 64.9% had a Karnofsky score of 80. Between before and one week following chemotherapy II, the respondents' blood creatinine and urea levels rose. The eGFR value has also decreased. Periostin levels, on the other hand, tended to rise one week following treatment III after declining during chemotherapy I and II (p value>0.05). Urine periostin levels and other kidney function indicators did not significantly correlate (p>0.05), according to the correlation test, and several domains had negative directions. The correlation coefficient values were modest (r = 0.017-0.254). There is a changing of urine periostin level of malignant patients receiving high dose cisplatin therapy which increase after the third chemotherapy. No significant correlation was found between periostin levels and kidney function in malignant patients with high-dose cisplatin therapy.